2021
DOI: 10.3390/cancers13092221
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Surgical Treatment Patterns for Colorectal Cancer in a Tertiary Medical Facility in Korea

Abstract: Because of their reluctance to visit the hospital due to concerns about contracting coronavirus disease 2019 (COVID-19), patients with colorectal cancer have been affected by delays in care during the pandemic. This study assessed the effects of the pandemic on the clinical characteristics and surgical treatment patterns of colorectal cancer patients at a tertiary medical facility in Korea. Patients who underwent colorectal cancer surgery at our institution between March and September 2020 were analyzed. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 29 publications
2
40
3
3
Order By: Relevance
“…Single site studies in Romania and Brazil and a larger studies in France, Australia and New Zealand found significantly more advanced new CRC cases after the pandemic broke out, but a single‐site South‐Korean study found no statistically significant difference in pTNM stage distribution after Covid19. 13 , 14 , 16 , 30 , 31 Single‐site studies cannot exclude the fact that patients could have gone to another provider for treatment, whereas our study includes the AP‐HP teaching hospitals in Paris region.…”
Section: Discussionmentioning
confidence: 99%
“…Single site studies in Romania and Brazil and a larger studies in France, Australia and New Zealand found significantly more advanced new CRC cases after the pandemic broke out, but a single‐site South‐Korean study found no statistically significant difference in pTNM stage distribution after Covid19. 13 , 14 , 16 , 30 , 31 Single‐site studies cannot exclude the fact that patients could have gone to another provider for treatment, whereas our study includes the AP‐HP teaching hospitals in Paris region.…”
Section: Discussionmentioning
confidence: 99%
“…After screening 283 abstracts generated by the search algorithm, 10 studies were deemed eligible for inclusion in the final quantitative analysis ( Figure 1 ). In total, 26,808 patients were incorporated in the analysis (19,152 in the pre-pandemic cohort and 7656 in the pandemic cohort), with five studies being from east Asia (one from Japan [ 14 ], two from China [ 15 , 16 ], and two from Korea [ 17 , 18 ]) and the remaining five from Europe (two from the United Kingdom [ 11 , 19 ], one from Italy [ 20 ], one from Ireland [ 3 ], and one from Serbia [ 21 ]). The size of the pandemic cohorts in each study was compared to that of the pre-pandemic cohorts after matching for the time duration of the data collection in the pandemic cohorts (in months).…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of patients who were treated with laparoscopic surgery increased from 54% to 58%, contrary to England [ 9 ] and Korea [ 10 ], who reported a decline in procedures performed with the minimally invasive technique during the COVID‐19 pandemic. In the international survey from covidsurg Collaborative, the proportion of laparoscopic surgeries were comparable to the Swedish numbers (57.2%) [ 23 ].…”
Section: Discussionmentioning
confidence: 98%
“…There is a scarcity in data regarding factual outcomes for colorectal cancer patients during the pandemic, with the majority of publications being recommendations [ 3 , 4 , 5 ], audits [ 6 ], surveys [ 3 , 7 ] and case reports [ 8 ]. A few population‐based studies have been published, reporting disruptions in the management of colorectal cancer in England [ 9 ], Korea [ 10 ], and Spain [ 11 ]. Also in Sweden, the pandemic put the healthcare system under severe strain, with tens of thousands of operations being postponed [ 12 ].…”
Section: Introductionmentioning
confidence: 99%